Asymmetric spread analysis of heart rate variability in XC mountain biking during a 20-minute autonomic profile test - Tafur-Tascón, L. J.; Martínez-Patiño, M. J.; Mina-Paz, Y. (Sensors, 2025)
The heart is innervated by the autonomic nervous system (ANS), which plays a role in regulating the heart rate. Cross-country mountain biking (MTBXC) is a sport with high physiological demands, where the autonomic nervous system plays a significant role. The main objective of this study was to analyze the asymmetry of heart rate in Colombian National Team mountain bikers, sub-23 category, during a 20 min cardiovascular autonomic profile test. Method: The cardiovascular autonomic profile was measured through heart rate variability during a 20 min test, divided into eight phases (supine, controlled ventilation at 10 cycles/min, controlled ventilation at 12 cycles/min, postural change, orthostasis, Ruffier test, 1 min recovery, and final recovery) in a group of n = 10 MTB cyclists from the National Sub-23 Team, including 5 males and 5 females. Results: The results for the male athletes were as follows: age: 19 ± 1 years; VO2max: 67.5 mL/kg/min; max power: 355 W; HRmax: 204 bpm. The results for the female athletes were as follows: age: 19 ± 1 years; VOmax: 58.5 mL/kg/min; max power: 265 W; HRmax: 194 bpm. Both genders showed the expected autonomic behavior in each phase. Asymmetrical propagation of heart rate was observed, with a greater deceleration pattern after postural changes and effort and a symmetrical acceleration pattern in these two phases. Discussion: Athletes exhibit increased vagal response compared to non-athletes. Mountain bikers show rapid heart rate reduction after exertion. Conclusion: This study demonstrates how mountain bikers exhibit increased heart rate deceleration following sympathetic stimuli.